Teaching Marx : the socialist challenge - Malott, Curry; Cole, Mike; Elmore, John M. (Critical constructions., 2013)
We are in the midst of yet another global crisis in capitalism. In the UK, we have the most right wing and ideologically driven government since Thatcher; a ruthless cabal of millionaires intent on destroying the welfare state. In the US, President Obama, whose initial record did not live up to the expectations of many on the Left, is increasingly driven by right-wing republicanism and other corporate interests. At the same time, there are developments in Latin America, in particular Venezuela, which are heralding the dawn of a new politics, and recovering the voice of Marx, but with a twenty-first century socialist focus, thus giving hope to the lives of millions of working people throughout the world. This is why the world media is intent on discrediting President Hugo Chávez; and insisting that ordinary people have to pay the cost of the crisis in capitalism. The Arab Spring and the Occupy movement also show signs of an anti-capitalist movement in embryo. In Greece, perhaps more than anywhere else in Europe (even France), the austerity-stricken working-classes are pushing for real existing socialism. It is therefore not surprising that the ruling class of Greece is increasingly supporting the neo-Nazi, fascist Golden Dawn party threatening civil war should they lose power as a class. Now is a prescient time to bring twenty-first century socialism to the educational institutions of the world, to teach Marx across the curriculum and across the globe.Through this volume our goal was to contribute to the literature by concretely demonstrating the practical implications of Marx's theory to curriculum. However, while this book provides concrete examples of how Marx can and has informed a revolutionary critical education, it is not intended to be prescriptive. That is, the chapters should not be read as a how to guide, but they should be taken as inspiration for new, creative approaches to Teaching Marx and interpreting and posing The Socialist Challenge.